1999
DOI: 10.1042/bj3410233
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial permeability transition pore and its role in cell death

Abstract: This article reviews the involvement of the mitochondrial permeability transition pore in necrotic and apoptotic cell death. The pore is formed from a complex of the voltage-dependent anion channel (VDAC), the adenine nucleotide translocase and cyclophilin-D (CyP-D) at contact sites between the mitochondrial outer and inner membranes. In vitro, under pseudopathological conditions of oxidative stress, relatively high Ca2+ and low ATP, the complex flickers into an open-pore state allowing free diffusion of low-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
1,281
4
50

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,811 publications
(1,357 citation statements)
references
References 207 publications
(285 reference statements)
22
1,281
4
50
Order By: Relevance
“…In addition, CKMT1 has been implicated in the regulation of the Ca 2 þ -induced mitochondrial permeability transition pore (PTP; O'Gorman et al, 1997). PTP is involved in triggering apoptosis by releasing proapoptotic factors into the cytosol (Crompton, 1999). Several studies have shown the aberrant expression of CKMT1 in cancers of various organs, including lung cancer, breast cancer, gastric cancer, colon cancer, and prostate cancer (DeLuca et al, 1981;Tsung, 1983;Kanemitsu et al, 1984;Wallimann et al, 1992), suggesting that CKMT1 is involved in the pathogenesis of various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CKMT1 has been implicated in the regulation of the Ca 2 þ -induced mitochondrial permeability transition pore (PTP; O'Gorman et al, 1997). PTP is involved in triggering apoptosis by releasing proapoptotic factors into the cytosol (Crompton, 1999). Several studies have shown the aberrant expression of CKMT1 in cancers of various organs, including lung cancer, breast cancer, gastric cancer, colon cancer, and prostate cancer (DeLuca et al, 1981;Tsung, 1983;Kanemitsu et al, 1984;Wallimann et al, 1992), suggesting that CKMT1 is involved in the pathogenesis of various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotransmitters released from adjacent neurons can generate slow depolarizing junctional potential which then can elicit an action potential through activating and then deactivating sodium-selective and potassium channels (Florczyk et al 2014). The voltage-dependent anion channel (VDAC) can assist the mitochondria with controlling cell death through releasing calcium, cytochrome c, and apoptosis-inducing factor from the mitochondria inner membrane space (Crompton 1999;Tsujimoto and Shimizu 2002). The coordination of Ca 2+ channels and Na + channels plays a vital role in regulating signal transduction pathways, including cell cycle and apoptosis.…”
Section: Neurochannelmentioning
confidence: 99%
“…In general, mitochondrial Ca 2+ overload and consequent mitochondrial dysfunction appear to be combining factors in excitotoxicity. They are playing key roles in cell death [64]. …”
Section: Signalling Roles Of Ca2+ and Rosmentioning
confidence: 99%